For the girls, gays, and theys: LGBTQ+ stakeholder communication and alignment of video game brands - Gaudszun, Isabell Charlott; Elmezeny, Ahmed (Frontiers in Communication, 2023)
Queer identities have predominantly existed at the peripheries of media representation as well as communication research. Linking this research gap with the field of video games as a medium this study examines video game companies and their strategic communication efforts towards LGBTQ+ stakeholders. With this focus we aim to identify how video game companies discursively construct queer identities and utilize them for strategic communication. Through the analysis of the social media and online discourses surrounding two games with queer inclusion, we show that queer branding has an influence on the way strategic communication efforts are employed throughout the year, as well as the type of content. Furthermore, we show that in our selected cases, organizations can successfully align themselves with their LGBTQ+ stakeholders through having queer inclusion at the core of their strategic communication efforts, and authentic organizational practices.